Monetary reward speeds up voluntary saccades - Chen, Lewis L.; Chen, Y. Mark; Zhou, Wu; Mustain, William D. (Frontiers in Integrative Neuroscience, 2014)
Past studies have shown that reward contingency is critical for sensorimotor learning, and reward expectation speeds up saccades in animals. Whether monetary reward speeds up saccades in human remains unknown. Here we addressed this issue by employing a conditional saccade task, in which human subjects performed a series of non-reflexive, visually-guided horizontal saccades. The subjects were (or were not) financially compensated for making a saccade in response to a centrally-displayed visual congruent (or incongruent) stimulus. Reward modulation of saccadic velocities was quantified independently of the amplitude-velocity coupling. We found that reward expectation significantly sped up voluntary saccades up to 30°/s, and the reward modulation was consistent across tests. These findings suggest that monetary reward speeds up saccades in human in a fashion analogous to how juice reward sped up saccades in monkeys. We further noticed that the idiosyncratic nasal-temporal velocity asymmetry was highly consistent regardless of test order, and its magnitude was not correlated with the magnitude of reward modulation. This suggests that reward modulation and the intrinsic velocity asymmetry may be governed by separate mechanisms that regulate saccade generation.